An Inhibitor of NF-κB and an Agonist of AMPK: Network Prediction and Multi-Omics Integration to Derive Signaling Pathways for Acteoside Against Alzheimer’s Disease - Li, Ying-Qi; Chen, Yi; Jiang, Si-Qi; Shi, Yuan-Yuan; Jiang, Xiao-Li; Wu, Shan-Shan; Zhou, Ping; Wang, Hui-Ying; Li, Ping; Li, Fei (Frontiers in Cell and Developmental Biology, 2021)
Alzheimer's disease (AD) is the most frequent type of dementia. While acteoside (ACT), a compound isolated from Cistanche tubulosa, possesses neuroprotective properties. However, the underlying mechanism in regulating microglia polarization remains ill-defined. A computational network model was established to identify the driving targets of ACT and predict its mechanisms by integrating multiple available databases. AlCl3-induced AD model in zebrafish larvae demonstrated the therapeutic efficacy of ACT. Subsequently, LPS-induced BV-2 cells uncovered the positive role of ACT in M1/M2 polarization. Finally, NF-κB and AMPK pathways were confirmed by transcriptomic analysis, metabolomics analysis, molecular biology techniques and molecular docking. The research provided an infusive mechanism of ACT and illustrated a new perspective based on mitochondrial dysfunction to reveal the connection between metabolism and microglia polarization. More importantly, it provided a systematic and comprehensive approach of drug target discovery, including the changes in genes, metabolites, and proteins.